We can solve these equations by using substitution method where you substitute one equation to the other and solve for the value of the other variable. We do as follows:
y = 2x^2
y = –3x −1
2x^2 = –3x −1
2x^2 +3x +1 = 0
x1= -0.5
x2 = -1
y1 = 0.5
y2 = 2
Answer:
(-6,-7)
Step-by-step explanation:
The third one is a point with the first equation.
I had to simplify the second equation.
It simplified to,
![y = - \frac{1}{4} x - 2](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B4%7D%20x%20-%202)
The second one with the above is didn't go through so I'd say no solution.